Etnosentrisme dan Sikap Intoleran Pendatang Terhadap Orang Papua - Elia Nurindah Sari; Samsuri Samsuri (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
This article is aimed to raising awareness for pluralistic Indonesian. Awareness to be able to appreciate anything about the differences in Indonesia, including those who are from Papua. Indonesia is now has any issues of tolerance. Although there are many public slogans or appelas to be tolerant, in fact not a few cases of intolerant attitudes occur. There are so many cases that lead to racism in Papuans. Ethnocentrism attitude told us how someone from a certain group feels better than another group. This will be linked to the intolerant attitudes to the Indonesian people towards Papuans, and learning study implications of what happened from that situation. The purpose of this article is to build awareness of all Indonesians to reduce their intolerant attitude towards Papuans. This article used the method of literature review. Some of the literature taken is, among others, related to the literacy of tolerance, Papuans culture and some cases of Indonesian intolernace towards Papuans. The results of research through this literature study found that intolerant cases carried out by non-Papuans against Papuans had implications or the attitude of Papuans who became inferior, lacked confident and felt unappreciated.